2020
DOI: 10.1055/a-1082-1372
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Maximum Accumulated Oxygen Deficit Using Backward Extrapolation

Abstract: This study aimed to compare the Maximum Accumulated Oxygen Deficit determined by the conventional method (MAODC) with that determined by the backward extrapolation technique (MAODEXTR) in runners. Fourteen runners underwent a maximal incremental test for determination of iVO2MAX, ten submaximal efforts (50–95% of iVO2MAX for 7 min). During the submaximal efforts oxygen consumption (VO2) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…For this, immediately after the effort, swimmers breathe in a face mask connected to the gas analyzer. Using this method, together with net lactate accumulation (Ana LA )—it is possible to determine anaerobic contribution in free swimming (AC FS ), as demonstrated previously (Campos et al, 2017a ; Andrade et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…For this, immediately after the effort, swimmers breathe in a face mask connected to the gas analyzer. Using this method, together with net lactate accumulation (Ana LA )—it is possible to determine anaerobic contribution in free swimming (AC FS ), as demonstrated previously (Campos et al, 2017a ; Andrade et al, 2021 ).…”
Section: Introductionmentioning
confidence: 84%
“…Finally, for the Ana ALA determination, 5 min of recovery was used. Bertuzzi et al ( 2016 ) have observed that a minimum of 6 min is required for Ana ALA evaluation; however, 5 min of recovery have been used in other studies (Kalva-Filho et al, 2015 ; Campos et al, 2017a ; Andrade et al, 2021 ), and the fast component happens in the 1st min of recovery. Moreover, studies could also use bi-exponential decay equation as proposed by Scheuermann et al ( 2011 )—since it does not assume that athletes will reach baseline values at the end of recovery—and compare Ana ALA using both Scheuermann et al ( 2011 ) and Ozyener et al ( 2001 ) equations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our laboratory published a study comparing supramaximal running efforts (110% of iV ̇O2MAX) using the traditional V ̇O2 collection (i.e. oronasal mask; restricted bouts) and with unimpeded efforts by the BE (de Andrade et al, 2020). The authors found a 16% improvement in time to exhaustion for BE group and pointed out due to the unrestricted access to ambient air and attenuated sensation of fatigue.…”
Section: When Citing Please Refer To the Published Versionmentioning
confidence: 99%
“…Due to its advantages, BE was applied in different modalities, including running (de Andrade et al, 2020), cycling (Sleivert and Mackinnon, 1991), swimming (Campos et al, 2017a;Campos et al, 2017b;Costill et al, 1985;Kalva-Filho et al, 2015a;Kalva-Filho et al, 2015b;Montpetit et al, 1981), kayaking (Carré et al, 1994), speed skating (Di Prampero et al, 1976), in female soccer This item was downloaded from IRIS Università di Bologna (https://cris.unibo.it/)…”
Section: When Citing Please Refer To the Published Versionmentioning
confidence: 99%
See 1 more Smart Citation